A clinical efficiency index for the measurement of hospital performance: development and validation - Cygańska, Małgorzata (Wskaźnik sprawności klinicznej do pomiaru dokonań szpitala: rozwój i walidacja, 2019)
Managers’ requirements for modern hospital performance measurement systems emphasize the need for including in the analysis clinical data. A hospital’s financial status cannot be fully and reliably evaluated without access to such data. The existing research concerning the hospital performance measurement systems using financial and non-financial data in the process of managing healthcare facilities is limited. Therefore the aim of the study was to develop a new measure - the clinical efficiency index - which can be used to evaluate the operational efficiency of a hospital based on both, costs and clinical factors. The study showed that conclusions drawn from financial analysis differs when covering clinical aspects. The main contribution of this work is to provide healthcare professionals with a more focused perspective towards incorporating clinical factors into the hospital performance measurement system
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 155-164
Keywords: hospital; performance measurement system; efficiency index; financial data; non-financial data; szpital; system pomiaru dokonań; wskaźnik sprawności; dane finansowe; dane niefinansowe